Transplant centers' prophylaxis and monitoring strategies: a key determinant of current herpes and polyomavirus incidences - results from the DZIF kidney transplant cohort - Sommerer, Claudia; Schröter, Iris; Gruneberg, Katrin; Schindler, Daniela; Morath, Christian; Renders, Lutz; Einecke, Gunilla; Guthoff, Martina; Heemann, Uwe; Schnitzler, Paul; Zeier, Martin; Giese, Thomas (BMC nephrology, 2025)
Herpes- and polyomaviruses are major opportunistic pathogens after renal transplantation. Despite established guidelines, there is limited data on transplant centers’ prophylaxis and monitoring strategies and centers’ adherence to these guidelines and their impact on infection rates and patient outcomes. This multicenter cohort study, conducted by the German Center for Infection Research, included 1035 kidney transplant recipients from five centers (01/2014-02/2021), focusing on herpes- and polyomavirus viremia within the first year and adherence to prophylaxis strategies. Among 1035 recipients, 26.6% developed herpes- or polyomavirus viremia, predominantly Cytomegalovirus (CMV, 14.3%) and BK-virus (BKV, 13.2%). BKV monitoring frequency was below guideline recommendations. Deviations from guidelines were most common in CMV D-/R- (34.6% with prophylaxis) and D−/R + groups (37.3% without prophylaxis), doubling CMV-incidence in D−/R+ (28.9% vs. 12.5%, p < 0.01). In D+/R − group, six-month-prophylaxis reduced CMV-incidence compared to three months (22.5% vs. 38.4%, p < 0.01). Breakthrough-viremia was most commonly observed in D+/R − recipients who received a six-month-prophylaxis. Overall, viremia was associated with higher incidence of acute rejection (31.9% vs. 17.6%, p < 0.01), with most CMV-viremias occurring after rejection. CMV-viremia was associated with a higher risk of bacterial infection (HR = 1.77, [1.03;3.02]). Other herpesviruses were associated with a quadrupled risk for fungal infection (HR = 4.34, [1.03;18.30]) and the non-administration of CMV-prophylaxis (HR = 0.22, [0.11;0.47]). Graft survival and mortality were unaffected within the first year. Clinical variability in guideline implementation drives high herpes- and polyomavirus infection rates with suboptimal outcomes. Future guidelines should focus on differentiated risk stratification to address breakthrough, post-prophylaxis, and post-rejection CMV, and include protocols for the early detection of secondary infections.